Cognition and cortical thickness in heavy cannabis users - Wittemann, Miriam; Brielmaier, Jule; Rubly, Mathias; Kennel, Jennifer; Werler, Florian; Schmitgen, Mike; Kubera, Katharina Maria; Hirjak, Dusan; Wolf, Nadine D.; Reith, Wolfgang; Wolf, Robert Christian (European addiction research, 2021)
Acute and long-term adverse effects of heavy cannabis use (HCU) on neurocognitive function have been suggested, as much as regional changes of brain volume. However, little is known about the relationship between impaired cognition and brain structure in individuals with HCU. Objective: Here, we investigated associations between cognition and cortical thickness (CT) in males with HCU and male controls. Methods: Twenty-six individuals with HCU and 20 controls were examined using a comprehensive neuropsychological test battery and high-resolution structural MRI at 3T. CT was calculated using the Computational Anatomy Toolbox (CAT12). Results: Individuals with HCU differed from controls with respect to verbal learning performance and verbal working memory only. Individuals with HCU showed reduced CT in medial temporal, orbitofrontal, and cingulate regions, as well as in areas of the middle temporal and fusiform cortex (peak voxel family-wise error-corrected p < 0.001, followed by empirically determined correction for spatial extent) compared to HC. Verbal learning performance was associated with right entorhinal and left orbitofrontal CT reductions. Entorhinal CT was also significantly associated with amount and frequency of current weekly cannabis use. Conclusions: The data support the notion of domain-specific cognitive impairment in individuals with HCU and provide a neuromechanistic understanding of such deficits, particularly with respect to abnormal CT in brain areas associated with long-term memory processing.